The effect of foot type on the Achilles tendon moment arm and biomechanics. (March 2019) - Deforth, Manja; Zwicky, Lukas; Horn, Tamara; Hintermann, Beat
Highlights: The average Achilles tendon moment arm was shorter for pes cavus than pes planus. The maximum Achilles tendon moment arm was found at different plantarflexion. The interrater reliability of alpha was higher on radiographs than on MRIs. Abstract: Background: The aim was to calculate the Achilles tendon moment arm in different degrees of plantarflexion for pes planus, pes cavus and normal arched feet. Methods: 99 patients (99 radiographs; 40 males, 59 females; mean age 49 years, SD 15) with a healthy ankle joint and a preoperative weightbearing lateral radiograph of the foot were included. Three groups (pes planus, pes cavus and normal-arched feet) with equal sample sizes (n = 33) were formed. On radiographs, the angle formed between a horizontal line and the line connecting the insertion of the Achilles tendon with the center of rotation of the ankle, was measured. The interrater reliabilities (ICC) of the angle alpha were compared on radiographs and on MRIs. Using the angle alpha, the Achilles tendon moment arm was calculated in different plantarflexion positions. Results: The ICC of alpha was higher on radiographs (0.84, [0.73–0.91]) than on MRIs (0.61, [0.27–0.81]). The average alpha was statistically significantly different (normal arched foot 31 degrees (°), pes planus 24°, pes cavus 36°, p = 0.021), resulting in a significant shorter Achilles tendon moment arm for pes cavus than for pes planus (p < 0.0001) and normal arched feet (p = 0.006) in neutral position. Conclusion: The data suggests that it is feasible to use radiographs to measure the Achilles tendon moment arm. The maximum Achilles tendon moment arm is reached at different angles of ankle flexion for pes cavus, pes planus and normal-arched feet. This has to be taken into consideration when planning surgeries.